2010
DOI: 10.1071/mf09227
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the great hammerhead shark, Sphyrna mokarran, in the north-western Atlantic Ocean and Gulf of Mexico

Abstract: The great hammerhead shark, Sphyrna mokarran, is a cosmopolitan species that is caught in a variety of fisheries throughout much of its range. The apparent decline of great hammerhead shark populations has reinforced the need for accurate biological data to enhance fishery management plans. To this end, age and growth estimates for the great hammerhead were determined from sharks (n = 216) ranging in size from 54- to 315-cm fork length (FL), captured in the Gulf of Mexico and north-western Atlantic Ocean. Grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
4
27
2
Order By: Relevance
“…g . bonnethead shark Sphyrna tiburo (L. 1758) (Parsons, ; Carlson & Parsons, ), blacknose shark Carcharhinus acronotus (Poey 1860) (Driggers III et al , 2004), great hammerhead Sphyrna mokarran (Rüppel 1837) (Piercy et al , ; Passerotti et al , ), tiger shark Galeocerdo cuvier (Péron & LeSeuer 1822) (Kneebone et al , ), sandbar shark Carcharhinus plumbeus (Nardo 1827) (Romine et al , ) and silky shark Carcharhinus falciformis (Müller & Henle 1839) (Joung et al , ; Hall et al , ). Nonetheless, recent validation studies have also confirmed that bands can form biannually in some species (Wells et al , ), irregularly in others (Huveneers et al , ) and can in some instances greatly underestimate true age (Kerr et al , ; Andrews et al , ; Natanson et al , ; Hamady et al , ).…”
Section: Discussionmentioning
confidence: 93%
“…g . bonnethead shark Sphyrna tiburo (L. 1758) (Parsons, ; Carlson & Parsons, ), blacknose shark Carcharhinus acronotus (Poey 1860) (Driggers III et al , 2004), great hammerhead Sphyrna mokarran (Rüppel 1837) (Piercy et al , ; Passerotti et al , ), tiger shark Galeocerdo cuvier (Péron & LeSeuer 1822) (Kneebone et al , ), sandbar shark Carcharhinus plumbeus (Nardo 1827) (Romine et al , ) and silky shark Carcharhinus falciformis (Müller & Henle 1839) (Joung et al , ; Hall et al , ). Nonetheless, recent validation studies have also confirmed that bands can form biannually in some species (Wells et al , ), irregularly in others (Huveneers et al , ) and can in some instances greatly underestimate true age (Kerr et al , ; Andrews et al , ; Natanson et al , ; Hamady et al , ).…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, Piercy et al (2007), who did run a MIA for all age classes in the North Atlantic ocean, concluded that one ring was formed yearly, and found k = 0.09 and 0.13 year -1 , for males and females respectively. Also Piercy et al (2010) using marginal increment analysis and a concurrent bomb radiocarbon validation study found annual band pair deposition for the great hammerhead, Sphyrna mokarran. A comparison of the present study with the growth curves obtained by different authors (Figure 4), indicated that S. lewini from the southern Brazilian coast grow slower and are more longevous than in the other regions studied until now.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen great hammerheads were detected on > 10 days, seven were tagged in Jupiter (3 female, 4 male) and 12 in Bimini (all female) (See Table 2 for further details). Most individuals were likely sexually mature based on Piercy et al (2010) and Miller et al (2014).…”
Section: Tagging Summarymentioning
confidence: 99%